Securing software development: A comprehensive and comparative analysis of cybersecurity measures - Sharma, Pawan Kumar (SADGAMAYA, 2024)
In the rapidly evolving digital age, the integrity and security of software development have emerged as paramount concerns amidst the increasing prevalence of cyber threats. This study presents a comprehensive and comparative analysis of cybersecurity measures within the software development lifecycle, focusing on a multi-layered technological framework comprising AWS hosting, Java Spring Boot backend, MySQL databases, Flutter/Dart frontend, and Android/iOS mobile applications, alongside RestAPIs. Through an adaptable methodology, this research delves into the cybersecurity challenges and solutions from both developers’ and users’ perspectives, underpinned by an empirical analysis supported by literature from AWS, OWASP Foundation, and SecureApps, among others. Central to our investigation is the dichotomy between the developer’s implementation strategies and the users’ expectations for security, aiming to uncover the extent of congruence between these two pivotal viewpoints. It also employs a mixed-method approach, integrating qualitative analyses with quantitative data to evaluate the effectiveness of current cybersecurity practices across different technological layers. By identifying key challenges and exploring real-world examples, this research endeavors to empower developers and stakeholders with actionable insights and recommendations to enhance cybersecurity measures effectively. The findings reveal a significant alignment between developers’ efforts and users’ expectations, in key areas of the subject. By fostering a deeper understanding of the cybersecurity landscape, this research aspires to guide the development of more resilient, secure software systems capable of withstanding the evolving threats in the digital ecosystem.